The Amination of Waste Newsprint Paper with Various Aminating Agents (Ammonia Water, Ethylenediamine, and Diethylenetriamine) to Improve the Sorption Efficiency of Anionic Dyes - Tomasz Jóźwiak (Molecules)
This study aimed to investigate the effect of aminating waste newsprint paper with different aminating agents (ammonia/ammonia water, ethylenediamine, and diethylenetriamine) for the sorption efficiency of Reactive Black 5 (RB5) and Reactive Yellow 84 (RY84) dyes. To increase the amination efficiency, the paper material was pre-activated with epichlorohydrin. The scope of this study included the characterization of the sorbents tested (FTIR, elemental analysis, BET surface area, porosity, and pHPZC), determination of the influence of pH on dye sorption efficiency, sorption kinetics, and the maximum sorption capacity of the dyes. The study results showed that amination with ethylenediamine and diethylenetriamine introduced 87% and 194% more amine groups into the sorbent’s structure compared to the treatment with ammonia. The sorption efficiency of RB5 and RY84 on the sorbents tested was the highest in the pH range of 2–3. The sorption equilibrium time ranged from 90 to 150 min and was longer in the case of the unmodified sorbents. The experimental data from the study were best described by the pseudo-second-order model and the Langmuir 1 and 2 models. Amination had a very strong effect on the sorption capacity of newsprint. For example, the sorption capacity of newsprint paper towards RB5 (Qmax = 7.12 mg/g) increased after amination with ammonia, ethylenediamine, and diethylenetriamine to the value of Qmax = 182.78 mg/g, Qmax = 202.7 mg/g, and Qmax = 231.5 mg/g, respectively.